2015
DOI: 10.1002/pts.2184
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions of Food Packaging: Contributing to or Counteracting Environmentally Sustainable Development?

Abstract: Packaging has a fundamental role in ensuring safe delivery of goods throughout supply chains to the end consumer in good condition. It also has great potential to contribute to sustainable development. This paper explores and provides insights on Swedish consumer perceptions and knowledge of environmental aspects of food packaging and elaborates on how these can contribute to or counteract environmentally sustainable development. A study based on a consumer survey carried out in Sweden is presented. A review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
211
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(234 citation statements)
references
References 76 publications
(273 reference statements)
17
211
1
5
Order By: Relevance
“…In this context, it is important to adequately convey the eco‐friendliness of the package. Indeed, research has shown that consumers are willing to pay a price premium when they are certain that the packaged product conveys certain qualities . Through style elements and environmental claims about the package, designers can enhance the understanding of environment‐friendly packaging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, it is important to adequately convey the eco‐friendliness of the package. Indeed, research has shown that consumers are willing to pay a price premium when they are certain that the packaged product conveys certain qualities . Through style elements and environmental claims about the package, designers can enhance the understanding of environment‐friendly packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Especially for food products, future studies should stress the influence of the package design on the product lifespan. Indeed, while organic or paper‐based packages positively influence perceptions of packaging and product environment‐friendliness, they might not provide optimal protection for the product, which would in turn increase the risk of wastage . Future experiments could adopt more global approaches and test the influence of the protective qualities of the product package (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So it is not surprising that research has identified both time pressure and cognitive overload together with a lack of willingness to process more information (Weinrich, Franz, & Spiller, ; Weinrich & Spiller, ) as factors limiting consumer selection of environmentally friendly packaging (Biel & Dahlstrand, ; Sheth, Newman, & Gross, ). In past studies, consumers have also expressed concern about their ability to judge packaging solutions (Lindh, Olsson, & Williams, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%